THE CONCEPT AND CRISIS ZONES OF RUSSIAN COGNITIVE LINGUISTICS - Sergei Ivanovich Krassa (Вестник Северо-Кавказского федерального университета)
The article discusses the concept as a crisisogenic factor in Russian cognitive linguistics. Crisis zones connected with understanding of the concept, the object domain, the structure of the concept, its name, and re- search methods are singled out.